ANALISIS PROPOSISI DENGAN METODE POHON SEMANTIK - Salwa Nursyahida (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The proposition is an argument or statement which has a truth value. Propositional Logic is a branch of Mathematical Logic that focuses on propositions and relations between them. Semantic tree (also known as truth tree, semantic tableau, or tableaux) is a method to grow truth-value assignment on trees. In this research article, the semantic tree method is used to analyze propositions and relations between propositions such as validity, consistency, equivalence, and logical entailment of propositions.